UJI TEGANGAN TEMBUS MINYAK ON LOAD TAP CHANGER DI GARDU INDUK 150KV RANGKAS BARU - Pasa Meliansyah; Didik Aribowo (Fakultas Teknik Universitas Maritim AMNI Semarang, 2022)
In transformers installed and used in electric power systems, especially at substations (GI) there are often disturbances or problems. One of the problems with the transformer can occur due to the failure of the insulating oil which can be caused by a decrease in the value of the translucent voltage, therefore it is necessary to carry out maintenance to prevent and localize interference. Tap Changer oil is different from oil in the main tank (in terms of placement), in terms of type and function Tap Changer oil with oil in the main tank has similarities from the type of oil and its function as insulation, cooling and protecting windings from oxidation. With the method of observation (observation) in the field of all equipment worked on and with the literature method can be known the process of replacing oil On Load Tap Changer. From the results of the oil translucent voltage test study, it is known that the value of the penetrating voltage of the On Load Tap Changer oil sample used in the transformer is an average value of 38.8 kV, it can be known that the value of the new oil penetrating voltage (sample 1) being filtered is 86.8 kV, the value of the new oil penetrating voltage (sample 2) being filtered is worth 88 kV, and the value of the new oil penetrating voltage (sample 3) being filtered is 98.2 kV.